Milestones In Diabetes Research - DHARSHINI. A, DIVYA; ROY, ANITHA; MURALIDHARAN. N.P (The journal of contemporary issues in business and government, 2020)
Diabetes is a lifestyle disease which grows epidemically at an alarming rate. Solomon Berson and Rosalyn Yalow measured how much insulin was in a diabetic’s blood which led to the discovery that some people with diabetes could still make insulin. There is Type-1 and Type-2 diabetes other than gestational diabetes . Diabetes is a mysterious illness with a wide array of complications. It has become a severe socio-economic burden on the developed and underdeveloped countries. It has been reported that half of the death is due to high blood sugar level. Despite many scientific milestones achieved in providing better healthcare facilities and in the treatment and mitigation of this disease, it still imposes a severe threat in countries with middle and low-level- income groups of population and many patients suffering from diabetes are still unable to achieve desired glycemic level. Recent explorations in drug discovery have opened new avenues in the development of new classes of drugs. Focusing on the emerging trends and advances in the field of diabetes treatment, the review will highlight the recent scientific and technological advancement in the development of newer generations of drugs or regimens over the past few decades.